Multifunctional drug delivery nanoparticles based on MIL-100 (Fe) for photoacoustic imaging-guided synergistic chemodynamic/chemo/photothermal breast cancer therapy. (November 2022) - Hu, Zhiming; Xu, Caina; Liang, Yonghao; Liu, Taiyuan; Tian, Huayu; Zhang, Yingchao
Graphical abstract: The developed multifunctional nanoparticles (DMTH NPs) were prepared by loading doxorubicin (DOX) into MIL-100 and then modified with tannic acid (TA) coordination and hyaluronic acid (HA) encapsulation, which could be used for chemodynamic/chemo/photothermal synergistic therapy guided by photoacoustic imaging (PAI) to obtain effectively antitumor therapy. Highlights: An innovative, multifunctional, drug-delivery nanoparticle (DMTH NP) was designed to achieve photoacoustic imaging-guided photothermal therapy, chemotherapy, and chemodynamic therapy for effective breast cancer theranostics. MIL-100(Fe) as the framework for the DMTH NP could catalyze H2 O2 into OH through a Fenton-like reaction to achieve chemodynamic therapy. The coordination complex of hydroxyl groups on tannin with iron ion provided photoacoustic imaging-guided photothermal therapy under laser irradiation in breast cancer. Hyaluronic acid in DMTH NP enabled tumor targeting ability, prolonged circulation time, and improved biocompatibility. Abstract: Compared with visceral cancers, breast cancer is epidermal and can be efficiently eliminated by photoacoustic imaging (PAI)-guided cancer therapy. In this study, we developed multifunctional nanoparticles (DMTH NPs) by loading doxorubicin (DOX) into MIL-100, which were modified with tannic acid (TA) and hyaluronic acid (HA) using a simple and convenient method. MIL-100 (Fe) in DMTH NPs allowed for chemodynamic therapy by converting endogenous hydrogen peroxide (H2 O2 ) into OH through a Fenton-like reaction to assist DOX in killing cancer cells. DMTH NPs had high DOX loading efficiency for chemotherapeutic function and had the ability for photoacoustic imaging (PAI) and photothermal therapy (PTT) after being modified by TA. Specifically, DMTH NPs targeted tumors and had low toxicity in vivo . Ultimately, the released DOX and OH cooperated in killing MCF-7 cells effectively in vitro . The enhanced and precise breast cancer treatment was achieved using a PAI-guided chemodynamic/chemo/photothermal synergistic therapy under laser irradiation in vivo . Overall, this work presented an innovative strategy for designing multifunctional nanoparticles for effective imaging-guided combination therapies to combat breast cancer.